Fingerprint Chromatography Analysis of Lentinan by PMP-HPLC and its Relationship with Immunoactivity - ZHAO Xiu-ting; ZHANG Yan-jie; FU Meng; LI Jin-wei; ZHU Song; FAN Liu-ping (Liang you shipin ke-ji, 2021)
A PMP-HPLC method for the determination of monosaccharide composition of Lentinan was established.Polysaccharide hydrolysates were performed on a Zorbax Eclipse XDB-C18 column, with a mobile phase consisting of 0.1mol/L phosphate buffer solution-ethyl alcohol (80:20 v/v) at the flow rate of 0.8 mL/min.The detector was ultraviolet detector (245 nm), and the column temperature was 30 ℃.Methodological studies showed that this method had high accuracy, reproducibility and stability, a good linear relationship in a certain concentration range (R2≥0.998 5) and a high sample recovery (80.6%～91.4%,RSD≤5%), so it could be applied to the analysis of monosaccharide composition of Lentinan.Through the analysis of 81 Lentinan samples, a PMP-HPLC fingerprint based on polysaccharide monosaccharide composition was constructed, and seven common characteristic peaks were identified, including fucose,glucosamine, galactose, glucose, mannose and xylose, with the similarity above 0.94.In addition, partial least squares regression (PLS) was used to analyze the correlation of Lentinan monosaccharide composition and the survival rate of RAW264.7 cells.The results showed that the glucosamine, ribose and glucose of Lentinan were positively correlated with the cell survival rate, and the former two had a higher correlation.